PROBLEMS AND PROSPECTS OF THE DEVELOPMENT OF THE INFORMATION TECHNOLOGY MARKET IN UKRAINE - KUSTOV, Vitaliy; TRYASHCHENKO, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the current issues that are preventing the development of the information technology market in Ukraine. It has been established that the leaders of the Ukrainian IT industry have already achieved significant success and have several undeniable achievements. The lack of a well-established state policy is preventing Ukraine from competing effectively in the global IT market as a producer of goods. The analysis of countries' global digital competitiveness ratings revealed that the world market of information technologies is segmented based on types, programs, and subtypes. Due to several factors, the information technology market in Ukraine has been growing moderately.Firstly, there is an increasing demand for advanced technologies and digitalization, along with positive trends in remote working, which is the usual mode for IT companies; secondly - the emergence of new information technologies and systems, products, IT services, and companies; thirdly, the development of the communications system, electronic payments, and e-commerce have also played a role in the market's expansion. Fourth, the increased digitalization in various sectors of the economy, including healthcare, government, finance, and education, is expected to drive the highest growth rates in the IT market; fifth, the growth of the IT market is also being fueled by the attraction of significant investments through progressive IT start-ups, sixth, the rapidly growing IT workforce. Lastly, there is an annual increase in the share of the Ukrainian IT market in the export of services.The effectiveness of the information technology market in Ukraine's export of services is presented through the dynamics of indicators from 2018 to 2022. Ukrainian IT companies should focus on further developing their information products to improve the situation. The article analyzes Ukraine's top 10 IT companies, where service companies dominate. It also summarizes the challenges that are hindering the development of the information technology market in Ukraine. Additionally, the article suggests directions that can help create a developed digital Ukrainian nation. Several measures are proposed to facilitate the rapid development of the information technology market in Ukraine. The first is to focus on building the world's first digital country, which involves ensuring secure and uninterrupted Internet access for all residents throughout the territory, this can be achieved by leveraging technologies like StarLink and other similar advancements. Secondly, there is a proposal to create a territory of innovation, which would involve technological integration and the introduction of new technologies. Thirdly, the development of high-tech and future-tech products is emphasized. Fourthly, the suggestion is to fully operate the virtual economy in parallel with the traditional one. Lastly, there is a proposal to attract major global services to Ukraine, such as global investment banks and Amazon services.
Keywords: information systems; information society; information technologies; IT services; IT sector; market; development